Role of machine learning and artificial intelligence in transforming aquaculture and fisheries sector - Maurya, Satyamvada; Kumar, Murali S; Kumar, Ravindra; Kushwaha, Basdeo (Indian Farming, 2024)
The rapid growth in the area of computer science has focused on creating machines that can perform tasks, such as visual perception, speech recognition, decision-making, and language translation, like human does. The two closely related fields of the computer science, viz. machine learning (ML) and artificial intelligence (AI), are revolutionizing the way we interact with the technologies.These technologies have ushered in a new era of technological possibilities for various industries, including fisheries and aquaculture. The future of ML and AI in aquaculture and fisheries holds promising advancements that will reshape the industry's landscape. This article focuses on the diverse applications of ML and AI in the fisheries sector, particularly for environmental monitoring, stock assessment and disease detection for enhancing the efficiency, sustainability and management of fisheries and aquaculture operations along with its limitations and the way forward. AI can help in better price discovery for fishermen and provide incentives for maintaining traceability, help policy makers to obtain the trend of aquaculture activities across the country and in identifying andresolving farmer issues more quickly.